Strengthening Open-Web Steel Joists - Fisher, James M. (Engineering Journal, 2005)
The paper presents procedures and suggested details for the strengthening of open web steel joists. Strengthening of open web steel joists is often required due to the addition of roof top units, under hung conveyors, or other loading increases not contemplated in the original specification for the joists. Three basic methods of strengthening a joist or joist system are discussed: load redistribution, adding new joists or beams, and reinforcing existing joists.